Is Life Support Competencies an Urgent Issue in Undergraduate Medical Education of Bangladesh? (Bangladesh Journal of Medical Education, 2024)
Background: Life support skills is the golden key for any emergency situation for survival of patient from endanger situation. Medical students, intern doctors and medical graduates learn from medical teachers and emergency consultants in the emergency care settings.Objectives- To identify the current life support competencies among the undergraduate medical students of Bangladesh.Methods: This cross-sectional study was conducted from July 2022 to June 2023 to identify the Life Support Competencies that the medical students and interns are acquiring /acquired. A self-administered semi- structured questionnaire was administered to collect data from conveniently selected 300 fifth year medical students and 321 interns, 114 recent graduate and 300 clinical teachers.Results: A 6 point semantic differentials scale was used to get the views of the respondents. Study revealed that out of 6- point scales (0-5) the mean of the respondent’s views regarding knowledge on management of life support competency were 1.77 to 3.06 but the means of the skilled based competencies were 1.15 to 2.75. The views of the recent graduates were statistically significantly lower on ten issues out of sixteen issues than other respondents groups.Conclusion: The medical students and interns are acquiring inadequate life support competencies in their courses. Necessary action to be taken to improve the competencies of medical students and interns on life support emergencies.BJME, Volume-15, Issue-01, January 2024: 1-2